Phenolic Compounds and Antioxidant Activity of Phalaenopsis Orchid Hybrids - Truong Ngoc Minh; Do Tan Khang; Phung Thi Tuyen; Luong The Minh; La Hoang Anh; Nguyen Van Quan; Pham Thi Thu Ha; Nguyen Thanh Quan; Nguyen Phu Toan; Abdelnaser Abdelghany Elzaawely; Tran Dang Xuan (MDPI AG, 2016)
Phalaenopsis spp. is the most commercially and economically important orchid, but their plant parts are often left unused, which has caused environmental problems. To date, reports on phytochemical analyses were most available on endangered and medicinal orchids. The present study was conducted to determine the total phenolics, total flavonoids, and antioxidant activity of ethanol extracts prepared from leaves and roots of six commercial hybrid Phalaenopsis spp. Leaf extracts of "Chian Xen Queen" contained the highest total phenolics with a value of 11.52 ± 0.43 mg gallic acid equivalent per g dry weight and the highest total flavonoids (4.98 ± 0.27 mg rutin equivalent per g dry weight). The antioxidant activity of root extracts evaluated by DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging assay and β-carotene bleaching method was higher than those of the leaf extracts. Eleven phenolic compounds were identified, namely, protocatechuic acid, p-hydroxybenzoic acid, vanillic acid, caffeic acid, syringic acid, vanillin, ferulic acid, sinapic acid, p-coumaric acid, benzoic acid, and ellagic acid. Ferulic, p-coumaric and sinapic acids were concentrated largely in the roots. The results suggested that the root extracts from hybrid Phalaenopsis spp. could be a potential source of natural antioxidants. This study also helps to reduce the amount of this orchid waste in industrial production, as its roots can be exploited for pharmaceutical purposes.